Optimization of Migration Time affected storage overheads during VM Live Migration using Network Attached Storage device (International Journal of Engineering and Computer Science, 2017)
Cloud computing has grown in relevant amount from recent years by inheriting a key feature of server virtualization which is the live migration of virtual machines(VMs). This technique mainly used in datacenters in order to provide cloud services without letting servers down by allowing a virtual machine from one system to another with minimum service interruption. Due to limited available network bandwidth, the network traffic get increases due to large amount of storage data which lead to create overheads during migration and hence increases migration time. This paper focuses on such type of duplicated data which consumes only unnecessary shared network bandwidth, increases migration time during live VM Migration and provide optimized solution using proposed scheme with the help of Network Attached Storage Device (NAS).